Characterizing Catchment‐Scale Nitrogen Legacies and Constraining Their Uncertainties. Issue 4 (12th April 2022) - Sarrazin, Fanny J.; Kumar, Rohini; Basu, Nandita B.; Musolff, Andreas; Weber, Michael; Van Meter, Kimberly J.; Attinger, Sabine
Abstract: Improving nitrogen (N) status in European water bodies is a pressing issue. N levels depend not only on current but also past N inputs to the landscape, that have accumulated through time in legacy stores (e.g., soil, groundwater). Catchment‐scale N models, that are commonly used to investigate in‐stream N levels, rarely examine the magnitude and dynamics of legacy components. This study aims to gain a better understanding of the long‐term fate of the N inputs and its uncertainties, using a legacy‐driven N model (ELEMeNT) in Germany's largest national river basin (Weser; 38, 450 km 2 ) over the period 1960–2015. We estimate the nine model parameters based on a progressive constraining strategy, to assess the value of different observational data sets. We demonstrate that beyond in‐stream N loading, soil N content and in‐stream N concentration allow to reduce the equifinality in model parameterizations. We find that more than 50% of the N surplus denitrifies (1480–2210 kg ha −1 ) and the stream export amounts to around 18% (410–640 kg ha −1 ), leaving behind as much as around 230–780 kg ha −1 of N in the (soil) source zone and 10–105 kg ha −1 in the subsurface. A sensitivity analysis reveals the importance of different factors affecting the residual uncertainties in simulated N legacies, namely hydrologic travel time, denitrification rates, a coefficient characterizing the protection of organic N in source zone and N surplus input. Our study calls for proper consideration of uncertainties in N legacy characterization, and discusses possible avenues to further reduce the equifinality in water quality modeling. Plain Language Summary: Lowering nitrogen (N) amounts in European surface waters is a pressing issue. N levels largely result from fertilizer application in agricultural areas, and deposition of atmospheric N coming from fossil fuel combustion. These N inputs to the landscape can accumulate below the ground surface in so‐called legacy stores (including the soil and aquifer), from which they can be released progressively through time. Therefore, N levels depend not only on the recent N inputs, but also on their history. Our modeling study aims to improve our understanding of the long‐term fate of the N inputs and its uncertainties in Germany's largest national river basin (Weser) over the period 1960–2015. It suggests that more than 50% of the N inputs to land is lost to the atmosphere (denitrification, 1480–2210 kg ha −1 ) and the stream export amounts to around 18% (410–640 kg ha −1 ), leaving behind as much as around 16% (264–820 kg ha −1 ) in the landscape (legacy). However, the uncertainties in these estimates remain large, partly due to a lack of observational data on internal (legacy) components and uncertainties in N inputs. Overall, our study calls for proper consideration of uncertainties in N legacy characterization, and discusses possible avenues to further reduce them. Key Points: We use a parsimonious model to examine the long‐term (1960–2015) fate of nitrogen inputs to the landscape including the legacy buildup More than 50% of the nitrogen surplus denitrifies and around 491 kg ha −1 accumulates in legacy stores in Germany's largest river basin Hydrologic travel time and denitrification rates largely contribute to the residual uncertainty in the simulated nitrogen legacies